APPLICATION OF BIOSYNTHESIZED NANOPARTICLES IN THE ENHANCEMENT OF GROWTH AND YIELD PERFORMANCES OF RICE (ORYZA SATIVA VAR. NERICA) UNDER SALINITY CONDITIONS IN A FERRUGINOUS ULTISOL (FUDMA JOURNAL OF SCIENCES, 2020)
The study was conducted to investigate the effects of application of biosynthesized silver nanoparticles (AgNPs) on the growth and yield performances of rice (Oryza sativa var. Nerica) under salinity conditions in a ferruginous ultisol. AgNPs were biosynthesized following standard procedure using leaves of Hibiscus sabderiffa. Viable rice seeds were sown in soils that were previously moistened with salt solution in 3 concentrations (100, 250 and 400mM). The AgNPs (200ml) was sprayed in five concentrations (5, 10, 15, 20 and 25% v/v) on the test plant for seven weeks. Morphometric parameters such as plant height, root number, leaf length and rice yield parameters were studied. Results showed that salinity significantly (p
Keywords: Silver nanoparticles, Enhancement, Salinity conditions, Ferruginous soil, rice